Reproductive effort in the Antarctic petrel Thalassoica antarctica : the effect of parental body size and condition - Lorentsen, Svein-Håkon (Norwegian Institute for Nature Research (NINA), 1995)
Keywords: Antarktis; fugler; ornitologi; petreller; reproduksjon; zoologi

Resource limitation in a long-lived seabird, the Antarctic petrel Thalassoica antarctica: a twining experiment - Andersen, Reidar; Sæther, Bernt-Erik; Pedersen, Hans Christian (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1993)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

Documentation of the demography and population monitoring systems for Antarctic Petrels at Svarthamaren, Dronning Maud Land - Lorentsen, Svein-Håkon; Røv, Nils; Bangjord, Georg (Norsk institutt for naturforskning, 1993)
During the Norwegian Antarctic Research Expedition 1991/92, four 9 x 15 m squares for long-term demographic studies and 201 study plots for population monitoring of Antarctic Petrels Thalassatca anlarctica were established at Svarthamaren (71" 53' S, 5' 10' E), Dronning Maud Land. This report details their geographical location at Svarthamaren.
Keywords: Dronning Maud Land; NARE 1991/92; antarktispetrell; bestandsovervåking; fugler; ornitologi; zoologi

Aspects of the breeding biology of the Antarctic Petrel Thalassoica antarctica and the krill requirement of the chicks, at Svarthamaren in Mühlig-Hofmanfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; krill; ornitologi; zoologi

Notes on the south polar skua Catharacta Maccormicki breeding at Svarthamaren in Mühlig-Hofmannfjella, Dronning Maud Land - Haftorn, Svein; Bech, Claus; Mehlum, Fridtjof (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi

The density of breeding and non-breeding Antarctic petrels at Svarthamaren, Dronning Maud Land, 1990 - Røv, Nils (Fauna Norvegica. Serie C. Cinclus, Norwegian Journal of Ornithology, 1991)
Keywords: Dronning Maud Land; forskning; fugler; ornitologi; zoologi